Sulfur contaminations inhibit depolymerization of Kraft lignin. (December 2019) - Daniel, Dideolu; Khachatryan, Lavrent; Astete, Carlos; Asatryan, Rubik; Marculescu, Cosmin; Boldor, Dorin
Abstract: Softwood Kraft lignin (s-KL) and methanol-fractionated extracted Kraft lignin (ex-KL) samples were thermally depolymerized via fractional (step-wise) pyrolysis at temperatures from 175 °C to 700 °C in an isothermal System for Thermal Diagnostic Studies (STDS) reactor. Major pyrolysis products include guaiacols, vanillins, phenols, syringols, and sulfur-containing compounds. Sulfur-containing compounds, as intrinsic contaminants (both adsorbed and covalently bound to KL matrixes), strongly inhibited the formation of pyrolysis products. The lesser the sulfur content in the KL matrix, the higher the yields of major pyrolysis products. The high yields and early release of tar components from pyrolysis of ex-KL were attributed to the initial pretreatment of s-KL (Soxhlet extraction in methanol) causing a decrease in sulfur content from 3.61% (s-KL) to 2.91% (ex-KL). Mechanistic explanations for the absence of sulfur-containing bio-oil products, inhibitory effect of sulfur-containing compounds, and the relatively high char content in depolymerization of both lignin substrates, are developed. Graphical abstract: Unlabelled Image Highlights: · Fractional pyrolysis of softwood Kraft (s-KL) and methanol-extracted (ex-KL) lignins at 175 o C - 700 o C was investigated Sulfur contaminants inhibit depolymerization of Kraft lignin during fractional pyrolysis Sulfur contaminants has dramatic effects on the production of bio-oil compounds · Mechanistic explanations of sulfur contaminations on depolymerization of both lignins are presented